COOPERATION BETWEEN CHINA AND RUSSIA IN THE CULTURAL SPHERE - Yuanhong, Xu (Journal of Oriental Studies, 2023)
This scientific article is devoted to the study of problems and prospects for the development of cooperation between Russia and China in the field of culture. The purpose of the research is to analyze the content and opportunities of Russian-Chinese cooperation in the field of culture, and the possibility of predicting the development of these relationships, considering the realities of modern world politics. Indeed, in the modern era of various crises, conflicts, and wars, the role of culture in international relations is an instrument of «soft power». States use this resource to promote their interests and improve mutual understanding between people. Cultural exchange has always occupied a special place in Russian and Chinese relations. In addition, since the middle of the 20th century, cultural diplomacy has become an integral part of the diplomatic relations between the two countries. The research methodology is based on the complex analysis of the materials. It is concluded that the prospects for the development of bilateral relations in the cultural sphere require new constructive ideas based on similar cultural values and cultural characteristics. The cyclical nature of the cultural interaction of countries causes the need to understand the processes of intercultural communication between them. Today, Russia and China declared a strategic partnership between the countries, and the cultural sphere is an essential guide. The development of cultural relations in general has a significant impact on the formation of a positive image of a neighbor. Key words: Culture, cultural sphere, cooperation, cultural exchange.